PROFESIONALISME KEPALA SEKOLAH SEBAGAI LEADER (Studi Situs SMP Negeri 1 Kalikotes Klaten) - Sulasminingsih , Sulasminingsih (2011)
This research general purpose is description of professionalism of headmaster as leader. Purpose of special description of ability characteristic to of headmaster leads educator energy and educational, ability of headmaster in decision making, ability of headmaster in communications two directions. This research approach is qualitative research, is research about data collected and expressed in the form of words compiled in sentence. Designs research to apply phenomenology Subject research is committee chief, headmaster, and teacher. Data collecting method applies in-depth interview, observation, and documentation. Analysis data analytical technique interactive. authenticity of data applies trianggulation technique. In implementation of management professional headmaster executes various efforts or activity managed professionally as according to vision, mission, and purpose of education of school and develops it dynamically causing reach purpose of which has been specified Headmaster as leader of education, in seeing from status and way of lifting pertained leader of opening, formal of leader, or status leader. Status leader can increase to become functional leader. Depended from achievement and ability in playing role it as leader of education as school which has been delivered responsibility to it. Despitefully, headmaster as leader of school must be able to give influences which can cause teacher moved to execute its(the duty is effectively so that performance they would better. As leader having influence, s(he tries that advise, suggestion and if the need of its(the command in follows by teachers. Thereby s(he can perform changes in way of think, position, behavior led by it. With excess owned by it is knowledge excess and experience, she assists teachers rounds into professional teacher. Success a leader in implementation of management of professionalism will succeed if the leader treat its(the others or subordinate is carefully, and gives motivation that they are performance which is high in executing duty, movement ability, gives motivation and influences people to ready does directional actions to attainment of purpose of through bravery takes decision about activity that is must be done